Coping with life during COVID-19: Modification in Mode of existence among health care workers of tertiary care hospital of Central Uttar Pradesh - Shukla, Sushil Kumar; Bajpai, Prashant Kumar; Kaushik, Amit; Kumar, Sandip; Chauhan, Mudit; Verma, Shailza; Pooja Pathak (Indian Journal of Community Health, 2025)
Introduction: As an emerging crisis, COVID-19 has impacted the lives of healthcare workers (HCWs) to a greater extent. As HCWs are carrying the heavy burden of treating patients, controlling the spread, and directly facing all the consequences, their lives have been jeopardized due to long shifts, fear of getting hands-on COVID-19 infection, and lack of time on one’s own to keep their individuality. Aim and objective: This study aimed to assess the impact of changes in the mode of existence on healthcare workers employed at a tertiary care rural facility in Central Uttar Pradesh, India, during the COVID-19 pandemic. Methodology: A cross-sectional study was conducted within one month of duration. The study included all the medical professionals in a tertiary care hospital of mid-Uttar Pradesh. Results: Most HCWs indulged in physical activities 90(86.5%) compared to during the COVID-19 pandemic 71(68.3%). Of the participants, 50(48.1%) felt anxious during the COVID-19 pandemic, while before the pandemic, it was only among 20(19.2%0) HCWs. Before the COVID-19 outbreak, most healthcare workers (HCWs) did not utilize face masks, with just 3.8% adhering to this practice. However, in light of the pandemic, the percentage of HCWs wearing face masks significantly rose to 64.4%. Before the Covid-19 pandemic, only a few HCWs were using the method of personal hygiene, 16(15.4%), 04(3.8%), 26(25.0%), and 12(11.5%), frequent handwashing, use of alcohol-based hand rub, frequent cleaning of places, and all methods of personal hygiene, respectively. Conclusion: From decreasing physical activities, increasing addictive behaviors and anxiety, and acclimatization in the new work environment to a daily lifestyle, collectively, the COVID-19 pandemic has affected HCW's existence considerably.